Laparoscopy shows superiority over endoscopy for early detection of malignant atrophic papulosis gastrointestinal complications: a case report and review of literature. Issue 1 (December 2015) - Toledo, A.; Shapiro, L.; Farrell, J.; Magro, C.; Polito, J.
Abstract Background The malignant form of atrophic papulosis (Köhlmeier-Degos disease) is a rare thrombo-occlusive vasculopathy that can affect multiple organ systems. Patients typically present with distinctive skin lesions reflective of vascular drop out. The small bowel is the most common internal organ involved, resulting in considerable morbidity and mortality attributable to ischemic microperforations. Determination of the presence of gastrointestinal lesions is critical in distinguishing systemic from the benign, cutaneous only disease and in identifying candidates for treatment. Case presentation We describe an 18 year old male who first presented with cutaneous atrophic papulosis but became critically ill from small bowel microperforations. He had an almost immediate and dramatic response to treatment. Prior to his presentation with acute abdomen he had upper and lower endoscopy showing areas of nonspecific patchy erythema. At laparotomy, innumerable characteristic lesions with central pearly hue and erythematous border were seen. PubMed was used for a literature search using the keywords malignant atrophic papulosis, Degos disease, endoscopy, laparoscopy and laparotomy. This search yielded 200 articles which were further analyzed for diagnostic procedures and findings. Among the 200 articles we identified only 11 cases in which endoscopy was performed. Results of endoscopy and laparotomy in our patient with malignant atrophic papulosis were compared to those in the literature. Endoscopy of the gastrointestinal tract has shown gastritis and non-specific inflammation whereas laparoscopy shows white plaques with red borders on the serosal surface of the small bowel and the peritoneum. From personal communications with other physicians worldwide, we identified three additional unpublished cases in which endoscopy revealed only minimal changes while laparoscopy showed dramatic lesions. From our experience the endoscopic findings are often subtle and nonspecific, whereas laparascopy or laparotomy will reveal pathognomic lesions on the serosal surface of the intestine. Conclusion Our report contrasts the endoscopic and laparoscopic findings in malignant atrophic papulosis which suggest laparoscopy is the more powerful means of detecting gastrointestinal involvement. Imaging studies may serve as a key indicator of systemic progression. Based on our experience, laparoscopy should be performed when there is a high index of suspicion for gastrointestinal malignant atrophic papulosis, even if endoscopic examination is non-diagnostic or normal.